The Effect of The Rupiah Exchange Rate on Inflation-Mediated Stock Prices in PT Unilever Indonesia Tbk - Resita Aprillia; Bangun Putra Prasetya (Journal Of Management Analytical and Solution (JoMAS), 2024)
Indonesia's large population presents significant opportunities for the consumergoods industry. However, a company's ability to sustain its stock price requirescareful consideration of macroeconomic variables. This study investigates theeffect of the Rupiah exchange rate on the stock price of PT Unilever IndonesiaTbk during the period from 2022 to 2023. Employing a quantitative approach,the research examines macroeconomic data, particularly the Rupiah exchangerate, obtained from Bank Indonesia. Using purposive sampling, the studyfocuses on data relevant to the research period. Multiple linear regressionanalysis is applied to assess the relationship between the Rupiah exchange rateand stock price. The findings reveal that the Rupiah exchange rate has asignificant impact on the stock price of PT Unilever Indonesia Tbk.